CHYLOTHORAX - Zafar, Arshad; Mohammad, Gul; Zaman, Ronaq (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: This is a case report of chylothorax in an adult man. The clinical features were pain in the right hypochondrium, fever and hepatomegaly. The chest X-ray showed right sided pleural effusion. Bio-chemical examination of aspirated fluid confirmed it to be CHYLE. A laparotomy and biopsy of mesenteric lymph node confirmed it to be tuberculous.